L’ultima critica: la scuola nella prospettiva della didattica critica - Franceschini, Giuliano (Studi sulla Formazione/Open Journal of Education, 2021)
Training systems are the last space available for criticism. The school is separated from the social context, it brings together pupils from different cultures, teaches obsolete content that is distant from the pupils' experience, uses pre-digital technologies. These characteristics, usually considered negative elements, can actually euncourage the development of critical thinking. These elements can be transformed into training opportunities trough critical teaching. Critical teaching intervenes on the organization of the educational context, on the space-time of training. The purpose of critical teaching is to form educated and supportive citizens, capable of actively participating in democratic life.